A practical framework for data management processes and their evaluation in population-based medical registries. (March 2013) - Sariyar, M.; Borg, A.; Heidinger, O.; Pommerening, K.
<x xml:space="preserve">Abstract</x> Introduction We present a framework for data management processes in population-based medical registries. Existing guidelines lack the concreteness we deem necessary for them to be of practical use, especially concerning the establishment of new registries. Therefore, we propose adjustments and concretisations with regard to data quality, data privacy, data security and registry purposes. Materials and methods First, we separately elaborate on the issues to be included into the framework and present proposals for their improvements. Thereafter, we provide a framework for medical registries based on quasi-standard-operation procedures. Results The main result is a concise and scientifically based framework that tries to be both broad and concrete. Within that framework, we distinguish between data acquisition, data storage and data presentation as sub-headings. We use the framework to categorise and evaluate the data management processes of a German cancer registry. Discussion The standardisation of data management processes in medical registries is important to guarantee high quality of the registered data, to enhance the realisation of purposes, to increase efficiency and to enable comparisons between registries. Our framework is destined to show how one central impediment for such standardisations – lack of practicality – can be addressed on scientific grounds.